Mechanical properties and tensile fracture of Ti–Al–V alloy strip under electropulsing-induced phase change. Issue 2 (15th December 2014) - Ye, Xiaoxin; Tse, Zion T.H.; Tang, Guoyi
Abstract: Abstract : The effect of high-energy electropulsing treatment (EPT) on the microstructure evolution, mechanical properties, and fracture behavior of as-treated Ti–6Al–4V alloy strips was investigated. EPT was found to accelerate phase transition and microstructure evolution of quasi-single-phase titanium alloy strips at a relatively low temperature, and obtain characteristic duplex microstructure and Widmanstatten microstructure. The EPT-induced microstructural changes increased elongation-to-failure remarkably with a slight decrease in tensile strength. Fracture surface observation and three-dimensional analysis showed that transition from small-shallow dimple colony to big-deep colony fracture took place with an increase in frequency of EPT. The rapid phase change of the Ti–6Al–4V alloy strip under EPT was attributed to the enhancement of nucleation rate and atomic diffusion resulting from the coupling of the thermal and athermal effects. It is supposed that EPT can provide a highly efficient method for the intermediate-softening annealing of titanium alloy sheet/strips.